Diseño y Construcción de una máquina despresadora para gallina asada en la empresa “Asadero Doña Miryam” - Pedraza Mora, Edwin Jair; Muñoz Ramirez, Diego Fernando (Universidad Antonio Nariño, 2023)
The design and construction of a depressing machine to be used exclusively for roast chicken in the company "Asadero Doña Myriam" is considered as an electromechanical prototype that meets an operational and control need in one of its segments of human activity in the handling of food. Since the development of the machine is generated as a result of internal factors of the company, it also allows a projection for application in industries of similar competitiveness. During the processes of schematization, design, construction and operation tests of the machine, financial, social and political factors are consigned that allow to elaborate a system that fulfills the minimum requirements in the food industry. Thus, the depressing process for roasted hen is complemented with a more innovative and less human labor project, taking into account the integration in a rural and urban environment that is constantly in technological inclusion. The construction models of this prototype were elaborated as a result of tests with errors and constant changes, either in some of its components or in modifications of its main systems, guaranteeing safety in the operation, hygiene in food handling and the correct functioning of each part. The diagrams and figures used were also captured with the support of an intelligent software known as SOLIDWORKS specialized in 3D design, guiding in a correct way each of these changes made in its final construction